Lions & sea lions & bears, oh my: utilizing museum specimens to study the ossification sequence of carnivoran taxa - Jonathan L. Sarasa; Alexander S. Okamoto; Mark A. Wright; Stephanie E. Pierce; Terence D. Capellini (BMC Zoology, 2024)
Abstract Background Mammalian skeletons are largely formed before birth. Heterochronic changes in skeletal formation can be investigated by comparing the order of ossification for different elements of the skeleton. Due to the challenge of collecting prenatal specimens in viviparous taxa, opportunistically collected museum specimens provide the best material for studying prenatal skeletal development across many mammalian species. Previous studies have investigated ossification sequence in a range of mammalian species, but little is known about the pattern of bone formation in Carnivora. Carnivorans have diverse ecologies, diets, and biomechanical specializations and are well-suited for investigating questions in evolutionary biology. Currently, developmental data on carnivorans is largely limited to domesticated species. To expand available data on carnivoran skeletal development, we used micro-computed tomography (micro-CT) to non-invasively evaluate the degree of ossification in all prenatal carnivoran specimens housed in the Harvard Museum of Comparative Zoology. By coding the presence or absence of bones in each specimen, we constructed ossification sequences for each species. Parsimov-based genetic inference (PGi) was then used to identify heterochronic shifts between carnivoran lineages and reconstruct the ancestral ossification sequence of Carnivora. Results We used micro-CT to study prenatal ossification sequence in six carnivora species: Eumetopias jubatus (Steller sea lion, n = 6), Herpestes javanicus (small Indian mongoose, n = 1), Panthera leo (lion, n = 1), Urocyon cinereoargenteus (gray fox, n = 1), Ursus arctos arctos (Eurasian brown bear, n = 1), and Viverricula indica (small Indian civet, n = 5). Due to the relatively later stage of collection for the available specimens, few heterochronic shifts were identified. Ossification sequences of feliform species showed complete agreement with the domestic cat. In caniforms, the bear and fox ossification sequences largely matched the dog, but numerous heterochronic shifts were identified in the sea lion. Conclusions We use museum specimens to generate cranial and postcranial micro-CT data on six species split between the two major carnivoran clades: Caniformia and Feliformia. Our data suggest that the ossification sequence of domestic dogs and cats are likely good models for terrestrial caniforms and feliforms, respectively, but not pinnipeds.